2019
DOI: 10.1159/000496754
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor Represses GnRH Gene Expression via cFOS during Inflammation in Male Mice

Abstract: Background: The mechanisms whereby neuroinflammation negatively affects neuronal function in the hypothalamus are not clear. Our previous study determined that obesity-mediated chronic inflammation elicits sex-specific impairment in reproductive function via reduction in spine density in gonadotropin-releasing hormone (GnRH) neurons. Neuroinflammation and subsequent decrease in GnRH neuron spine density was specific for male mice, while protection in females was independent of ovarian estrogens. Methods: To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 125 publications
1
11
0
Order By: Relevance
“…Of interest, Gria4 gene for AMPA 4/GluR4 glutamate receptor was repressed specifically in HFD-fed males, whereas Grm2 coding for mGLUR2 metabotropic glutamate receptor 2, and Grin2b coding for NMDA receptor 2B, were repressed specifically in HFD-fed females. As we demonstrated before [ 9 , 53 ] and consistent with previous studies [ 54 , 55 ], GnRH (gonadotropin-releasing hormone) gene, critical for reproductive function, was repressed specifically in HFD-fed males. TRH (thyrotropin-releasing hormone), which causes increased thyroid hormone levels leading to a higher metabolic rate [ 56 ], was upregulated only in HFD-fed females.…”
Section: Resultssupporting
confidence: 90%
“…Of interest, Gria4 gene for AMPA 4/GluR4 glutamate receptor was repressed specifically in HFD-fed males, whereas Grm2 coding for mGLUR2 metabotropic glutamate receptor 2, and Grin2b coding for NMDA receptor 2B, were repressed specifically in HFD-fed females. As we demonstrated before [ 9 , 53 ] and consistent with previous studies [ 54 , 55 ], GnRH (gonadotropin-releasing hormone) gene, critical for reproductive function, was repressed specifically in HFD-fed males. TRH (thyrotropin-releasing hormone), which causes increased thyroid hormone levels leading to a higher metabolic rate [ 56 ], was upregulated only in HFD-fed females.…”
Section: Resultssupporting
confidence: 90%
“…We demonstrated that females are protected from immunological changes in cytokine levels and neuroendocrine changes in hormone levels regardless of the gonadal status. For example, males on an HFD have increased levels of TNF-a, LIF, and IL-6, whereas in females, unmodified or ovariectomized, TNF-a and LIF are unchanged (19,20). This may indicate that chromosomal differences contribute to intrinsic sex differences in the immune system.…”
Section: Sex Differences In Macrophage Responses To Obesity-mediated ...mentioning
confidence: 99%
“…The reason for this discrepancy between the present study and those published studies remains to be determined. By far, although considerable studies have shown that hypothalamic inflammation affected the HPG axis and thus the reproductive system in various inflammation models (Lainez and Coss 2019a;Wu and Wolfe 2012), the underlying mechanism remains elusive. The present study demonstrated in mice that the POMC neurons but not the AgRP neurons mediated the disruption of the HPG axis and thus the sperm production by the hypothalamic inflammation due to PM 2:5 exposure, providing a deep insight into the mechanism for the action of hypothalamic inflammation on the HPG axis and subsequently sperm production.…”
Section: Discussionmentioning
confidence: 99%